2017
DOI: 10.1016/j.cam.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

A front-fixing numerical method for a free boundary nonlinear diffusion logistic population model

Abstract: The spatial-temporal spreading of a new invasive species in a habitat has interest in ecology and is modeled by a moving boundary diffusion logistic partial differential problem, where the moving boundary represents the unknown expanding front of the species. In this paper a front-fixing approach is applied in order to transform the original moving boundary problem into a fixed boundary one.A finite difference method preserving qualitative properties of the theoretical solution is proposed. Results are illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To overcome this shortcoming of (1.3), Du and Lin [29] introduced a free boundary version of the Fisher equation (1.1), where the equation for u(t, x) is satisfied over a changing interval (g(t), h(t)), representing the population range at time t, together with the boundary condition uðt; xÞ ¼ 0 for x 2 fgðtÞ; hðtÞg, and free boundary condition They showed that this modified model always has a unique solution and as time goes to infinity, the population u(t, x) exhibits a ''spreading-vanishing dichotomy'', namely it either vanishes or converges to 1; moreover, in the latter case, a finite spreading speed can be determined. This work has motivated considerable research, and the ''spreading-vanishing dichotomy'' discovered in [29] has been shown to occur in a variety of similar models; see, for example, extensions to equations with a more general nonlinear term f(u) [31,59,60] etc., extensions to equations with advection [52,58,83] etc., extensions to systems of population or epidemic models [1,30,40,53,68,80,82] etc., and development of numerical methods for treating some of these free boundary problems [69,70,72] etc.…”
Section: Nonlinear Stefan Problemsmentioning
confidence: 99%
“…To overcome this shortcoming of (1.3), Du and Lin [29] introduced a free boundary version of the Fisher equation (1.1), where the equation for u(t, x) is satisfied over a changing interval (g(t), h(t)), representing the population range at time t, together with the boundary condition uðt; xÞ ¼ 0 for x 2 fgðtÞ; hðtÞg, and free boundary condition They showed that this modified model always has a unique solution and as time goes to infinity, the population u(t, x) exhibits a ''spreading-vanishing dichotomy'', namely it either vanishes or converges to 1; moreover, in the latter case, a finite spreading speed can be determined. This work has motivated considerable research, and the ''spreading-vanishing dichotomy'' discovered in [29] has been shown to occur in a variety of similar models; see, for example, extensions to equations with a more general nonlinear term f(u) [31,59,60] etc., extensions to equations with advection [52,58,83] etc., extensions to systems of population or epidemic models [1,30,40,53,68,80,82] etc., and development of numerical methods for treating some of these free boundary problems [69,70,72] etc.…”
Section: Nonlinear Stefan Problemsmentioning
confidence: 99%
“…To explore the influence of the change of a parameter on the number of population, we design an experiment to explore the three factors, that is, the initial population size, the population growth rate and the environmental maximum capacity [4]. We will take paramecium as the experimental biology sample.…”
Section: Methodsmentioning
confidence: 99%
“…In general, it is always difficult to handle the attraction term in chemotaxis system which may lead to convection dominant in the system [4], [20], [21], [28]. However, in the system (1), we have extra numerical challenges in efficiently and accurately handling the moving boundaries [26]. These two challenges require us to construct a new numerical algorithm in the numerical study.…”
Section: Numerical Logistic Type Chemotaxis Systems With a Free Boundary 1087mentioning
confidence: 99%